2003
DOI: 10.3136/fstr.9.345
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Boysenberry Anthocyanins on Oxidative Stress in Diabetic Rats

Abstract: The protective effects of major boysenberry anthocyanins (BoAnt) against oxidative stress were investigated in streptozotocin (STZ)-induced diabetic rats. Increases in the concentration of plasma thiobarbituric acid reactive substances (TBARS), and in the liver 8-hydroxy deoxyguanosine (8-OH dG)/deoxyguanosine (dG) ratio and also in the liver GSSG/GSH ratio, which were all observed in STZ-injected rats, were restored or tended to be restored to the level of the control rats when a diet with BoAnt was given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the inhibition or reduction of oxidative processes, as additional therapy, can prevent or delay the onset of complications associated with diabetes (Bonina et al, 2002). This prevention can be accomplished with the use of antioxidants and also through the increased expression of antioxidant enzymes; the administration of ANT can be effective in such circumstances (Feshani et al, 2011;Sugimoto et al, 2003).…”
Section: Oxidative Stressmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the inhibition or reduction of oxidative processes, as additional therapy, can prevent or delay the onset of complications associated with diabetes (Bonina et al, 2002). This prevention can be accomplished with the use of antioxidants and also through the increased expression of antioxidant enzymes; the administration of ANT can be effective in such circumstances (Feshani et al, 2011;Sugimoto et al, 2003).…”
Section: Oxidative Stressmentioning
confidence: 98%
“…Several experiments have demonstrated the antidiabetic properties of ANTs, which are attributed to multiple and simultaneous effects of these bioactive compounds, including reducing blood glucose, glucosuria and Hb A1c; preventing free radical production; increasing insulin secretion; and improving insulin resistance (Ataie-Jafari, Hosseini, Karimi, & Pajouhi, 2008;Grace et al, 2009;Guo et al, 2007;Iwai, Onodera, & Matsue, 2004;Jayaprakasam, Vareed, Olson, & Nair, 2005;Roy et al, 2008;Sugimoto, Igarachi However, some studies with healthy, non-diabetic humans revealed that ANT did not alter blood glucose or plasma insulin concentrations (Basu et al, 2009;Chambers & Camire, 2003;Kelley et al, 2006), perhaps because it requires the presence of pre-existing metabolic disorders for which these compounds have an effective action.…”
Section: Properties Of Anthocyanin-related Type 2 Diabetesmentioning
confidence: 98%
See 1 more Smart Citation
“…The mice were kept under controlled conditions with a 12-h light and 12-h dark cycle (6:00-18:00 light) in a temperature range of [22][23][24] C and a relative humidity of 40-60%.…”
mentioning
confidence: 99%
“…The tricloromethyl radical produced from carbon tetrachloride by its dechlorination from the action of cytochrome P450 isozymes is thought to induce the formation of the lipid radical and consecutive lipid peroxidation to finally cause liver cell damage. 15) Leaves of atsumi-kabu (2.7 kg dry weight), which had been dried in a room at about [20][21][22][23][24][25] C with ventilation, were extracted with methyl alcohol (MeOH) under reflux. The evaporated extract was dissolved in MeOH and mixed with chloroform and distilled water in the ratio of 0.5:1:2 (v/v/v).…”
mentioning
confidence: 99%